Can Wage Subsidies Boost Employment in the Wake of an Economic Crisis? Evidence from Mexico - Bruhn, Miriam (World Bank E-Library Archive, 2016)
The rise in unemployment during an economic crisis poses a significant concern to policy makers. This paper measures the effect of a program in Mexico that granted firms in certain industries wage subsidies if they decided to keep their workers instead of letting them go during the recent economic crisis. The analysis uses monthly administrative data on employment at the industry level, along with propensity score matching to construct groups of eligible and ineligible durable goods manufacturing industries that display statistically identical pre-program trends in employment. Difference-in-difference results show a positive but not statistically significant effect of the wage subsidies on employment during the program's eight-month duration, ranging from 5.7 to 13.2 percent in magnitude, depending on the specification. The size of the effect increases to 24 percent after the program ended and the results indicate that employment after the program recovered faster in eligible industries than in ineligible industries